Crohn’s disease: Etiology, pathogenesis and treatment strategies - BAŞOĞLU, İZEL AYCAN (My University, 2023)
Crohn’s disease (CD), which can be localized in any part of the gastrointestinal tract, is a disease characterized by an irregular immune response to normal and/or abnormal microbial antigens. Recent studies show many extensive data about the roles of genetic and environmental factors, immune function, and gut microbiota in CD. Although, less invasive biomarkers are currently being developed, the diagnosis of the disease is still based on the endoscopy and histological evaluation of biopsy samples. The most common symptoms are diarrhea, abdominal pain, weight loss, and fatigue. Despite the improvements in the treatment methods in the last decade, there is no definitive treatment since the etiology of CD is not known exactly. Therapeutic strategies focus on reducing inflammation and symptoms, maintaining clinical remission, and improving quality of life.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Crohn’s Disease; Inflammatory bowel disease; Intestinal microbiota; Nutrition therapy